Analisis Faktor Faktor yang Mempengaruhi Kedisiplinan Guru dalam Proses Pembelajaran di SDN 06 Sungai Nanam - Enjelita Putri; Jasrial . (CV. ITTC INDONESIA, 2025)
This study aims to analyze the factors influencing teacher discipline in the learning process at SDN 06 Sungai Nanam. Teacher discipline is an essential component in achieving educational goals because it affects classroom order, student learning outcomes, and the effectiveness of the teaching process. This research employed a descriptive quantitative method by distributing questionnaires to teachers. The questionnaire measured discipline in aspects such as punctuality, adherence to school rules, teaching readiness, completion of learning administration, and professional responsibility. The findings indicate that teacher discipline is categorized as very good, with a total score of 276 and a dominance of “Strongly Agree” responses. The contributing factors include school leadership, work motivation, work environment, professional commitment, and school culture. These results highlight that teacher discipline is not only related to presence and punctuality, but also reflects professionalism and the work culture established within the school environment.